Introductory algebra and related topics for technicians - King, Kenneth A. (Englewood Cliffs, New Jersey : Prentice-Hall, 1979)
This book, consisting of small learning units, on Introductory algebra and related topics for technicians, is a combination of a traditional textbook and an individualized programmed workbook.
Keywords: ALGEBRA